The Relationship between Serum CXCL8 and ET-1 Expression Levels and Sepsis Complicated with Heart Failure - Jianlong Zhu; Changjun Song; Tingting Cai; Lulu Yi; Wei Zhang; Jing Zhong; Meirong Shen (Cardiology Research and Practice)
Objective. The objective is to investigate the relationship between sepsis complicated with heart failure and the expression levels of CXC chemokine ligand 8 (CXCL8) and endothelin-1 (ET-1). Methods. A total of 128 sepsis patients accepted by the Ganzhou People’s Hospital from March 2019 to December 2021 were collected as observation objects, and they were separated into a simple sepsis group (86 cases) and a complicated heart failure group (42 cases) according to whether they were accompanied by heart failure or not. General data such as Sequential Organ Failure Assessment (SOFA) score and Acute Physiology and Chronic Health Evaluation II (APACHE II) were collected; the expression levels of serum CXCL8 and ET-1 were detected by enzyme-linked immunosorbent assay (ELISA); the cardiac function parameters such as left ventricular ejection fraction (LVEF), stroke volume (SV), cardiac output (CO), and cardiac index (CI) were measured by color Doppler ultrasound; the correlation between serum CXCL8 and ET-1 expression levels with clinical data and cardiac function parameters in patients with sepsis complicated with heart failure was analyzed by the Pearson correlation; and the influencing factors of sepsis complicated with heart failure were analyzed by the logistic regression analysis. Results. The serum CXCL8 and ET-1 expression levels, SOFA score, and APACHE II score in the complicated heart failure group were higher than those in the simple sepsis group (P<0.05), and LVEF, SV, CO, and CI in the complicated heart failure group were lower than those in the simple sepsis group (P<0.05). Serum CXCL8 was positively correlated with ET-1 in patients with sepsis complicated with heart failure (r = 0.531, P<0.05), and the two were positively correlated with SOFA score and APACHE II score (P<0.05) and were negatively correlated with LVEF, SV, CO, and CI (P<0.05). CXCL8 and ET-1 were independent risk factors for sepsis complicated with heart failure (P<0.05). Conclusion. The expression levels of serum CXCL8 and ET-1 in sepsis patients with heart failure are significantly increased, and both are risk factors for heart failure in sepsis patients.